2015
DOI: 10.1039/c4sc03804e
|View full text |Cite
|
Sign up to set email alerts
|

Development of solvent-free synthesis of hydrogen-bonded supramolecular polyurethanes

Abstract: A solvent free ball-milling method for the synthesis of small molecule and oligomeric carbamates is described that is applicable to supramolecular polymer synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 58 publications
0
20
0
5
Order By: Relevance
“…34 A conceptually distinct class of polymeric adhesive that can debond on command are those that contain supramolecular non-covalent interactions which form a reversible network. 35 Thermoresponsive supramolecular adhesives utilising hydrogen bonding 22,[36][37][38][39][40][41] have been demonstrated, in addition to those that harness metal/ligand interactions which were responsive to both light and heat. 22 An additional functionality that can be built into these systems is the ability to undergo a permanent reduction in tensile modulus/adhesion strength which persists after the stimulus has been removed.…”
Section: Introductionmentioning
confidence: 99%
“…34 A conceptually distinct class of polymeric adhesive that can debond on command are those that contain supramolecular non-covalent interactions which form a reversible network. 35 Thermoresponsive supramolecular adhesives utilising hydrogen bonding 22,[36][37][38][39][40][41] have been demonstrated, in addition to those that harness metal/ligand interactions which were responsive to both light and heat. 22 An additional functionality that can be built into these systems is the ability to undergo a permanent reduction in tensile modulus/adhesion strength which persists after the stimulus has been removed.…”
Section: Introductionmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) showed that the microphase separation structure was formed through intermolecular hydrogen bonding. If the content of hydrogen bond can be increased, the microphase separation can be further promoted, and the mechanical performance of the system can be improved (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Numerous polyols have been harnessed as building blocks, however, from the range of commercially available isocyanates, methylene diphenyl diisocyanate (MDI) has found the most extensive use on account of its attractive chemistries and relatively low toxicity. 11,12 A recent development in PU chemistries has been the investigation of supramolecular polyurethane (SPU) networks [13][14][15][16][17][18] which are able to self-assemble through weak non-covalent interactions. [19][20][21][22][23][24][25][26][27] These materials are attractive on account of their thermo-reversible characteristics.…”
Section: Introductionmentioning
confidence: 99%